Modified OFDM Receiver Design with Improved Channel Capacity - Anil Kumar, R.; K. Satya Prasad, Dr. (International Journal of Engineering and Technology, 2018)
High data transmission rate, reliability and spectral efficiency are necessary for developing wireless communication systems for real time seamless audio and video transmission. To find the impact of wireless channel on OFDM signal, channel estimation plays a major role. In this paper, implementation of pilot assisted channel estimation and performance analysis of the CFO and STO are investigated and estimated. Distinctive channel estimation techniques like Least Square (LS), Minimum Mean Square Error estimator (MMSE) and proposed MMSE strategies are discussed and furthermore, this paper focuses on performance juxtaposition of the channel, CFO and STO estimation with reference to Symbol error rate and Mean square error. If the mean square error is higher for low SNR sub-channels, then allocate power by using water filling algorithm to increase the channel capacity of the users.Â Â